Consumers’ Perception and Attitude Towards Nutrition Labelling in Tehran, Iran - Rezai, Golnaz (2005)
The impending international challenges facing Iran will continue to be dominant and affect its economic prospect considerably. With an increasing trend towards globalization, Iran would be faced with sweeping technological changes in food manufacturing that requires the altering of methods and ways of conducting their businesses. The emergence of new competitors is fostering competition, opening new markets and expanding existing ones. It is prudent that authorities in Iran seriously consider having regulations for nutrition labelling in order to become competitive in the global market. Nutrition label is one aspect of food labelling. It is a food label providing nutrition information concerning nutrient and energy values per designated size portion. The principle reason for nutrition labelling is that the consumers have a right to know what is in the purchased foods so that consumers can make better decisions for their own well being and that of their children. Although public concern and apprehension about nutritious diet have increased recently, much of the debate about healthy food has been at a scientific level where the technical words used are not easily understood by the general public. The objective of this research is to find the degree of awareness and utilization of nutrition labelling by consumers in order to determine the factors that influence consumers to read labels. In the survey, 1200 respondents were interviewed to determine their awareness, perceptions and attitudes towards nutrition labelling. Descriptive analyses, Chisquare analysis, factor analysis and regression logistic method were applied in analysing the data. The descriptive analysis was used to discuss the socio-economics profile in terms of distribution and percentage. The awareness, attitude and perception analysis towards nutrition label used the same technique in term of percentage and mean. Cross tabulations were applied to identify the relationship between demographic factors and nutrition label in the different aspects. The factor analysis is a general scientific method for analyzing data. It utilizes a linear approach to the reduction and summarization of data and comprises a large set of techniques with similar purpose. The regression logistic model was applied to determine the correlation between reading nutrition label and being influenced by source of nutrition information. In general, the findings show that the majority of the consumers have heard about nutrition labels and once a while they check or read the nutrition information, but only a ratio of the consumers have a right perception towards nutrition labels. However, most consumers buy food products which has nutrition label, but only a small portion of them purchase food product based on information is written on the nutrition label. The survey reveals that majority of consumers believe that food product which carry nutrition label is healthier. The study also found that there are relationships between demographic factors and perception towards nutrition labelling on the food products in different aspects. Based on factor analysis, eight factors were identified that can influence the purchasing food products based on nutrition label. These factors were as follows; utilizing nutrition labelling, degree of awareness, trust ability, product price, health conscious, safe conscious, and government involvement and manufactured practiced. The study concluded that the Iranian government should make use of education as a medium to introduce nutrition labelling policies and launch promotions on healthy aspects through mass media to improve the awareness of consumers. The government has to control and encourage the producers who look at nutrition label as solution to introducing standard manufactured foods or developing the product at international level. The producers and processors should be provided with enough knowledge on how to put right and correct nutrition labelling by following the rules and regulations of international norms. Consumers should also be aware and understand the importance of nutrition labelling and how this information can influence their future purchasing and untimely affect their health.